THE CONSUMMATED SWINDLE OF THE GOVERNANTS WITH THE SUPPORT OF THE ELITES IN COMPULSORY/AUTOMATIC PROGRESSION: IN THE NAME OF A "VILE/SORDID/REVENUE-COLLECTING" EXEGESIS AGAINST THE LOWER CLASSES THAT DEPEND ON PUBLIC EDUCATION UNDER A CRITICAL LOOK AT THE HISTORICAL AND ANTHROPOLOGICAL HERMENEUTICS OF THE JURIDICAL-PEDAGOGICAL IMPACTS ON THE EDUCATION OF OUR TUPINIQUIM STUDENTS IN TERRA BRASILIS (International Integralize Scientific, 2026)
The compulsory progression, imposed by the MEC, is a pedagogical scam that violates the Federal Constitution and the LDB, allowing students to be approved without mastering basic skills, devaluing individual effort and meritocracy. The LDB (Law 9.394/96) establishes that education is a fundamental right and a duty of the State, but the MEC's interpretation has allowed students to be approved without mastering basic skills, violating the law and attacking meritocracy. The compulsory progression has serious consequences, including cumulative cognitive deficit, student body demotivation, decrease in teacher authority, and loss of education quality. It is necessary to restore the sovereignty of the Class Council and the teacher's authority, and retention is a necessary educational pedagogical instrument to ensure the quality of education. This article aims to critically analyze the distorted hermeneutics of the LDB and its impacts on Brazilian intellectual and legal capital. The methodology used is documentary and bibliographic analysis, focusing on Brazilian educational legislation and academic production on the subject. The results demonstrate that compulsory progression has serious consequences, including cumulative cognitive deficit, student body demotivation, decrease in teacher authority, and loss of education quality. In conclusion, it is necessary to restore the sovereignty of the Class Council and the teacher's authority, and that retention is a necessary educational pedagogical instrument to ensure the quality of education.
Keywords: Pedagogical scam; compulsory progression; distorted hermeneutics; LDB; meritocracy.